2015
DOI: 10.1016/j.bmc.2015.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relationships of substituted 1H-indole-2-carboxamides as CB1 receptor allosteric modulators

Abstract: A series of substituted 1H-indole-2-carboxamides structurally related to compounds Org27569 (1), Org29647 (2) and Org27759 (3) were synthesized and evaluated for CB1 allosteric modulating activity in calcium mobilization assays. Structure-activity relationship studies showed that the modulation potency of this series at the CB1 receptor was enhanced by the presence of a diethylamino group at the 4-position of the phenyl ring, a chloro or fluoro group at the C5 position and short alkyl groups at the C3 position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…22, 24 In these assays, CHO cells that overexpress the promiscuous Gα 16 protein (RD-HGA16 cells, Molecular Devices) were engineered to stably express the human CB1 or CB2 receptor. Compounds were evaluated for their ability to inhibit the mobilization of intracellular calcium levels stimulated by CP55,940.…”
Section: Resultsmentioning
confidence: 99%
“…22, 24 In these assays, CHO cells that overexpress the promiscuous Gα 16 protein (RD-HGA16 cells, Molecular Devices) were engineered to stably express the human CB1 or CB2 receptor. Compounds were evaluated for their ability to inhibit the mobilization of intracellular calcium levels stimulated by CP55,940.…”
Section: Resultsmentioning
confidence: 99%
“…These conformation-restricted moieties might cause steric interference when the ligands bearing these photophores interact with the CB1 allosteric site. In earlier SAR studies, it was also found that cyclic substituents on the 4-position of the phenyl ring of this scaffold was not as tolerated as acyclic substituents [3234]. The results of 28 and 29 showed that azido and TFMD moieties located at the 4-position of the phenyl ring indeed reduced the binding capacity of the ligands to the allosteric site of CB1 receptor.…”
Section: Resultsmentioning
confidence: 96%
“…An n-propyl chain substitution enhances the allosteric modulation of orthosteric ligand binding, whereas an n-hexyl chain enhances the affinity of the allosteric modulator for CB 1 (Khurana et al, 2014). Substitution with short chain alkyl groups such as methyl improves allostery at CB 1 in calcium mobilization assays (Nguyen et al, 2015). …”
Section: Allosteric Modulators Of the Cb1 Receptormentioning
confidence: 99%
“…A fluoro substitution at the C5 position demonstrates improved allostery over a chloro substitution (Nguyen et al, 2015). …”
Section: Allosteric Modulators Of the Cb1 Receptormentioning
confidence: 99%
See 1 more Smart Citation